Chronic basilar artery dissection with an associated symptomatic aneurysm presenting with massive subarachnoid hemorrhage. (August 2016) - Cohen, José E.; Moscovici, Samuel; Rajz, Gustavo; Vargas, Andres; Itshayek, Eyal
Highlights: Isolated dissection of the basilar artery is rare but has been reported. Aneurysm rupture in an unruptured basilar artery dissection is exceptional. Basilar artery dissection may present with major or minor symptoms, or be asymptomatic. Patients are often inadequately diagnosed and thus prone to late complications. Close follow-up is warranted to rule out aneurysm formation. Abstract: Basilar artery dissection (BAD) is a rare condition with a worse prognosis than a dissection limited to the vertebral artery. We report a rare case of chronic BAD with an associated symptomatic aneurysm presenting with massive subarachnoid hemorrhage (SAH) in a 54-year-old woman. The diagnosis of acute BAD could only be made retrospectively, based on clinical and neuroradiological studies from a hospital admission 10 months earlier. Angiography performed after her SAH showed unequivocal signs of imperfect healing; she was either post-recanalization of a complete occlusion or post-dissection. Residual multi-channel intraluminal defects led to the development of a small aneurysm, which was responsible for the massive hemorrhage. The occurrence of an associated aneurysm, and wall disease, but not an intraluminal process, reinforces the diagnosis of dissection. The patient was fully recovered at 90 day follow-up. This case reinforces the need for long-term neuroradiological surveillance after non-hemorrhagic intracranial dissections to detect the development of de novo aneurysms.